Optimization of a clearing and staining protocol for the study of skeletal development in chame (Dormitator latifrons) (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The chame fish (Dormitator latifrons) is highly relevant to aquaculture and artisanal fisheries in Ecuador. Considering the limited baseline biological information available for this species, its morphology and development were studied here using the clearing and staining technique, which allows skeletal observation through transparent tissues. Juvenile chame specimens measuring 9–16 cm (n = 6) was treated with 0.1 N KOH to clear soft tissues, and two bone-staining pigments were evaluated: Red No. 40 and Alizarin Red. Alizarin Red showed greater specificity for bone tissue due to its affinity for calcium, providing better results in the visualization and identification of skeletal structures. In addition, bone calcification was observed in all analyzed size classes, suggesting that this process begins before 9 cm in length. This optimized protocol therefore constitutes an effective tool for the study of fish species with similar size and anatomy.